Ethics and Sustainability During Challenging Times - Mohamed Saat, Maisarah; Mohd. Jamal , Noriza; Azman, Sariati (International Journal of Psychosocial Rehabilitation, 2020)
A prominent economist has cautioned that SMEs in Malaysia should be ready and brace themselves for tough economic times ahead. Weak ringgit, labour shortages, and rises in prices of products and services are conditions that SMEs are now trying to deal with. Thus, this research first attempts to seek the opinion of SMEs owners on the effect of the current economy on their businesses. Secondly, it tries to investigate the importance and effect of business ethics on SMEs business and lastly to identify factors and challenges of SMEs to sustain during economic challenging times. A total of 45 small business owners were interviewed in an urban area of Johor Bahru. It is found that the current tough times of the economy have generally affected the small businesses. Some really struggled in their endeavour to sustain their business. Although misconducts were being admitted by the owners in cutting corners, the majority of them are concerned with customers’ trust and loyalty, thus perceived that business ethics should not be compromised. They also agreed that strengthening business relations, particularly with customers and suppliers, is vital to ensuring business sustainability. It is also recommended that small businesses leverage technology and seriously move into automation in order to face current and future challenges.